Glucocorticoid receptors in human peripheral blood mononuclear cells in relation to explosive performance in elite handball players - Bonifazi, M.; Bosco, C.; Colli, R.; Lodi, L.; Lupo, C.; Massai, L.; Muscettola, M. (Life Sciences, 2001)
Ten handball players, members of the Italian National Team (aged 20-25 years), were studied in two sessions corresponding to different performance levels. The first session occurred one week after the end of the regular season of the Italian Handball Federation: it corresponded to the beginning of the training cycle for the European Handball Championship. The second session occurred ten weeks after the first session. During this period, training consisted of 3 weeks of active recovery and 7 weeks of increasing workload. For each session, jumping performances (maximal height in a single jump, average mechanical power for a 15-s set of consecutive jumps) were evaluated. Venous blood samples were collected in resting conditions immediately before jumping performances to assess cortisol and testosterone plasma concentrations and glucocorticoid receptors (GcR) binding capacity and affinity in peripheral blood mononuclear cells (PBMCs). All the parameters, except GcR binding affinity, increased in the second session. The trends of variation in jumping performances, steroid hormone levels and GcR binding capacity were similar. For testosterone, this agrees with the hypothesis that an adequate level of this hormone is a prerequisite for improvement in explosive performances. For cortisol, higher GcR binding capacity after 10 weeks of training (with respect to initial values) indicated an up-regulation of GcR concomitant with the increase in hormone levels and performances. These findings suggest that the adaptation to training, confirmed by the improvement in performance, is characterized by a high value of GcR binding capacity and that it is mediated, among other factors, by the hormone levels and up-regulation of the receptors.